The Influence Of Service, Price, And Product Quality On Consumer Purchase Intention For Mixue Ice Cream & Tea - Fitri, Riskilia Aida; Anggarini, Desy Tri (SEAN Institute, 2025)
This study examines the influence of service, price, and product quality on consumer purchase intentions for Mixue Ice Cream and Tea. Using a quantitative approach and multiple linear regression analysis, data were collected through online questionnaires from 40 respondents in Probolinggo City. The findings reveal that price and product quality significantly influence purchase intentions, while service does not show a significant impact when analyzed individually. However, collectively, these three variables positively and significantly affect purchase intentions. These results highlight the importance of integrating competitive pricing, consistent product quality, and excellent service in marketing strategies to optimize consumer appeal and market competitiveness.